Measurement and Evaluation of the Online Marketing Training Results for Students at SMA Negeri 1 Bantur, Malang - M. Arief Bustomi; Ali Yunus Rohedi; Muchammad Nurif (Institut Teknologi Sepuluh Nopember, 2021)
SMA Negeri 1 Bantur, Malang Regency is located in the southern areaof Malang Regency. The demographic conditions and characteristicsof theBantur community have caused many Bantur 1 SMA graduatesto choose to work rather than continue their education to highereducation. As a solution to this condition, the school has provided jobtraining to students for one year as a provision for them aftergraduation. Apart from being in the form of student knowledge andskills, job training activities also produce goods and services that canbe marketed to the public. Therefore, after participating in the trainingactivities, SMA Negeri 1 Bantur students need to also be given trainingin marketing goods and services. This paper presents the results oftraining activities for the marketing of goods and services online atSMAN 1 Bantur. The methods used in the training are tutorials andpractice using textand video media. Measuring the success of trainingactivities using a questionnaire method and direct assessment of theresults of the training participants' practice. The research objectivewas to obtain a measure of the success of online marketing trainingactivities at SMA Negeri 1 Bantur. Theresults of measuring the successof training and their evaluation can measurethe increase in knowledgeand skills of each student who participates in the training.